Digital guided implant placement: optimizing positioning with consideration for hard and soft tissue - a case report - Cahyadi Lioe, Benedict; Ariesanti, Yessy (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Tooth loss can lead to functional and aesthetic disturbances in the oral cavity. The placement of dental implants is an effective solution in restoring oral function and aesthetics. Advancements in technology have allowed for digital pre-surgical planning and fully guided implant placement, enabling precise and optimal outcomes. The aim of this case report is to describe the treatment steps in implant placement with a fully guided digital approach. Case Report: The patient presented with a complaint of a missing lower right tooth and desired a permanent dental prosthesis. The patient had no significant history of systemic diseases or allergies. After clinical and radiographic examinations, a treatment plan was established for dental implant placement in tooth 46. The treatment plan included digitally designing a surgical guide and utilizing the fully guided technique for implant placement. The surgical procedure was performed in two stages. The first stage involved implant placement. The second stage involved gingival augmentation and placement of a healing abutment. Subsequently, the patient underwent the prosthetic phase, including fabrication of a monolithic zirconia implant crown, and crown insertion. Conclusion: The dental implant treatment provided the patient with satisfactory aesthetics and functionality. The utilization of the fully guided technique, augmentation using existing soft tissues, and the selection of an appropriate crown material yielded favourable results. Proper pre-operative planning, consideration of biological factors such as hard and soft tissues, and a prosthetic-driven approach are crucial for achieving successful dental implant placement.